Evaluation of butorphanol–azaperone–medetomidine (BAM) in captive blesbok immobilization (Damaliscus pygargus phillipsi). (July 2018) - Semjonov, Aleksandr; Andrianov, Vladimir; Raath, Jacobus P.; Orro, Toomas; Laubscher, Liesel; Pfitzer, Silke; Tiirats, Toomas
Abstract: Objective: The fixed-dose combination of butorphanol, azaperone and medetomidine (BAM; 30, 12 and 12 mg mL −1, respectively) with subsequent antagonism by naltrexone–atipamezole was evaluated for reversible immobilization of captive blesbok ( Damaliscus pygargus phillipsi ). Study design: Prospective, clinical trial. Animals: Sixteen blesbok (four males and twelve females), weighing 52.5−71.0 kg, were immobilized in South Africa. Methods: The total dose of BAM ranged from 0.5 to 0.7 mL for females and 0.7 to 0.9 mL for males. In seven animals chosen randomly, 8000 units of hyaluronidase was added to the dart. Physiologic variables were recorded every 5 minutes beginning at 10−20 minutes after darting. Arterial blood samples were collected three times at 20, 30 and 40 minutes after darting for analysis of blood acid-base status. Results: The mean administered doses of BAM were as follows: butorphanol (0.34 ± 0.08 mg kg −1 ), azaperone (0.14 ± 0.03 mg kg −1 ) and medetomidine (0.14 ± 0.03 mg kg −1 ). The inductions were calm and smooth. The mean induction time was 9.6 ± 3.2 minutes with just BAM and 5.1 ± 0.8 minutes with BAM and hyaluronidase combination. Heart rate (45 ± 6 beats minute −1 ) and respiratory frequency (38 ± 4 breaths minute −1 ) were stable throughout immobilization. The mean arterial blood pressure for all animals was stable but elevated (137 ± 7 mmHg). Rectal temperature slightly increased over time but remained within an acceptable range. The recovery time after administering naltrexone and atipamezole was 4.8 ± 0.7 minutes. Conclusion and clinical relevance: The BAM combination proved to be reliable and effective in blesbok.